Overweight, obesity and adiposity in survivors of childhood brain tumours: a systematic review and meta‐analysis. Issue 1 (11th October 2017) - Wang, K‐W.; Fleming, A.; Johnston, D. L.; Zelcer, S. M.; Rassekh, S. R.; Ladhani, S.; Socha, A.; Shinuda, J.; Jaber, S.; Burrow, S.; Singh, S. K.; Banfield, L.; et al.
Summary: Survivors of childhood brain tumours (SCBT) have increased cardiometabolic risks, but the determinants of these risks are unclear. This systematic review aims to compare the prevalence of overweight and obesity as well as adiposity measures between SCBT and non‐cancer controls. The PubMed, EMBASE, MEDLINE, CINAHL and the Cochrane Library databases were searched. The primary outcomes were the prevalence of overweight and obesity based on body mass index. The secondary outcomes were adiposity measures including percent fat mass, waist‐to‐hip and waist‐to‐height ratios. Forty‐one studies were included in the meta‐analysis. The prevalence of overweight and obesity combined was similar between overall SCBT, SCBT excluding craniopharyngioma and non‐cancer controls (42.6%, 95% CI 30.1–55.1 vs. 31.7%, 95% CI 20.4–43.0 vs. 40.4%, 95% CI 34.0–46.8). We also found that SCBT have higher percent fat mass (mean difference 4.1%, 95% CI 2.0–6.1), waist‐to‐hip ratio (mean difference 0.07, 95% CI 0.02–0.13) and waist‐to‐height ratio (mean difference 0.06, 95% CI 0.01–0.10) than non‐cancer controls. We conclude that SCBT have similar overweight and obesity distribution but higher adiposity than non‐cancer controls. More studies were needed to explore the determinants of adiposity and its contribution to cardiometabolic outcomes in SCBT.